Application and application method of an oxygen vacancy type g-C3N4@TiO2 heterojunction

CN116990380BActive Publication Date: 2026-10-09SHANDONG ANALYSIS AND TEST CENTER
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310717950.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2026-10-09
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

[0007]针对现有技术存在的不足,本发明的目的是基于新型氧空位型异质结纳米材料的低背景干扰、高吸光率、低载流子复合率及优异的吸附性能,结合LDI/MS的分析及LDI/MSI成像分析的优势,建立低质荷比小分子化合物的分析及成像新方法,运用该方法成功解决了传统有机基质及单一基质的多种缺陷问题,推动新型纳米基质向更快速、高效的方向发展

Benefits of technology

(1)本发明设计了一种异质结构纳米基质制备方法,制备了新型氧空位g-C3N4@TiO2异质结,并首次用于LDI-MSI。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116990380B_ABST
    Figure CN116990380B_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on g-C3N4@TiO2 oxygen vacancy heterojunction matrix for antibiotic small molecule drug LDI / MS analysis and imaging (LDI / MSI) method of laser desorption ionization / mass spectrometry (LDI / MS).The g-C3N4@TiO2 heterojunction used in the method has the advantages of low background interference, high durability, high stability, high sensitivity and high dispersion uniformity compared with traditional organic matrix.At the same time, the existence of heterostructure can also avoid the problems of light absorption rate difference and carrier rapid recombination caused by single nanomatrix.The obtained g-C3N4@TiO2 heterojunction can not only be used for LDI / MS detection of quinolone antibiotic drugs in environmental water samples, LDI / MS detection of endogenous small molecules in Danshen, but also can be uniformly dispersed into film on ITO conductive glass for imaging analysis of antibiotic drug pollution in traditional Chinese medicine.This invention provides a new method for the detection of small molecule compounds in complex samples and the distribution detection of pollutants and endogenous small molecule compounds in traditional Chinese medicine, and also provides a new idea for the development of new nanomatrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the application of composite nanomaterials, and in particular to the application and application method of an oxygen vacancy type g-C3N4@TiO2 heterojunction. Background Technology

[0002] my country, a populous country, faces a particularly significant problem of antibiotic overuse. After treatment, antibiotics are excreted through wastewater, which enters the aquatic environment, causing serious pollution. In recent years, antibiotic residues in the aquatic environment have received widespread attention. Antibiotics in the aquatic environment can be absorbed by plants and animals, entering the bodies of organisms and subsequently affecting human health. Studies have shown that quinolone antibiotic residues can be detected in various crops and cash crops, including lettuce, tomatoes, carrots, spinach, and reeds. Reeds and lotus roots, as two aquatic plants, not only have ornamental value, but their roots, rhizomes, and nodes also have medicinal value. Imaging the root systems of these two plants can not only analyze water and soil pollution but also their medicinal active ingredients, providing new insights for environmental protection and the analysis of the distribution of active ingredients in traditional Chinese medicine.

[0003] Laser desorption / ionization mass spectrometry (LDI-MS) has attracted widespread attention since its development due to its advantages such as rapid analysis, small sample volume, and high-throughput detection. However, traditional organic acid matrices, such as α-cyano-4-hydroxycinnamic acid (CHCA), sinapic acid (SA), and 2,5-dihydroxybenzoic acid (DHB), produce strong background noise interference in the low mass range (m / z < 1000 Da), which severely limits the application of LDI / MS in small molecule detection and imaging (MSI). Furthermore, analyte-matrix mixtures tend to form heterogeneous crystals on the sample plate, resulting in different intensities of mass spectral peaks from the same sample point. Therefore, it is necessary to develop novel matrices to address these issues.

[0004] In recent years, the application of nanomaterials in LDI / MS has attracted widespread attention. Carbon-based nanomaterials, metal / metal oxides, metal-organic frameworks (MOFs), and organic covalent frameworks (COFs) have been successfully applied to the LDI / MS analysis of small molecules. Using them as matrices can effectively reduce background interference. These solid matrices assist in desorption and ionization through various laser-induced thermal and electronic processes, such as photothermal conversion, heat transfer, and photoinduced charge carrier generation. Among various nanostructures, TiO2 nanostructures are widely used as solid matrices. The band gap energy of TiO2 semiconductors is ≈3.2 eV, comparable to the wavelength of the N2 laser (355 nm) commonly used in LDI-MS. Therefore, using photoinduced charge carriers can achieve optimal ionization efficiency. Various types of TiO2 nanostructures have been used in LDI-MS, including nanotubes, nanowires, and nanoparticles. However, the method of using TiO2 as a solid matrix still has the following problems: 1) high recombination rate of photoinduced charge carriers and 2) poor photothermal effect. The existence of these problems affects the ionization efficiency of the analyte and the mass spectrometry response.

[0005] This invention combines TiO2 with graphene-type nitrogen carbide (g-C3N4), overcoming the limitations of pure TiO2 and enabling efficient LDI-MS analysis of small molecule compounds. Improving TiO2 performance primarily involves material design from the perspectives of interfaces and vacancies. Interface engineering mainly utilizes nanocomposite methods to form homogeneous or heterogeneous interfaces, achieving carrier separation and transport through the resulting homojunction or heterojunction structures. Vacancy engineering focuses on improving TiO2 properties by controlling oxygen or titanium vacancies. Oxygen-vacant TiO2 is synthesized and simultaneously combined with g-C3N4 to form a heterojunction structure. The presence of oxygen vacancies in TiO2 enhances carrier transport rates and expands the photoresponse range. Due to its narrow band gap (2.7 eV) and matched band structure, g-C3N4, when combined with TiO2, exhibits better light absorption in the resulting composite material, also enabling effective separation of photogenerated carriers. The formation of heterojunctions and oxygen vacancy defects can reduce the charge loading rate of TiO2 carriers, increase the specific surface area of ​​the material, improve the photothermal effect, promote the desorption and ionization of the analyte, and realize efficient LDI / MS analysis of small molecule compounds.

[0006] This invention utilizes g-C3N4@TiO2 heterojunctions as a matrix for high-performance liquid chromatography-mass spectrometry (LDI / MS) analysis of three quinolone drugs in wastewater. The presence of g-C3N4 increases the specific surface area of ​​the matrix, accelerates mass transfer, enhances light absorption, increases the rate of photogenerated charge-hole transfer, and reduces recombination probability. Using g-C3N4@TiO2 as a matrix effectively improves the matrix's specific surface area, thermal conductivity, light absorption, and photoelectric transfer efficiency, thereby increasing the ionization efficiency and ionization intensity of the analytes, achieving efficient, rapid, and high-throughput analysis. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the purpose of this invention is to establish a new method for the analysis and imaging of low mass-to-charge ratio small molecule compounds by combining the advantages of LDI / MS analysis and LDI / MSI imaging analysis, based on the low background interference, high absorbance, low carrier recombination rate and excellent adsorption performance of novel oxygen vacancy heterojunction nanomaterials. This method successfully solves many defects of traditional organic matrices and single matrices, and promotes the development of novel nanomatrices towards a faster and more efficient direction.

[0008] This invention is achieved through the following technical solution: An application of an oxygen vacancy-type g-C3N4@TiO2 heterojunction: The synthesis of a g-C3N4 / TiO2 heterostructure for mass spectrometry detection and analysis of small molecule antibiotic compounds, and imaging analysis of the distribution of pollutants and endogenous substances in traditional Chinese medicine.

[0009] This invention also provides a method for applying oxygen vacancy-type g-C3N4@TiO2 heterojunctions, comprising the following steps: (1) The carbon nitride precursor powder was directly calcined at high temperature to obtain a yellow solid product, and washed several times with deionized water to remove the unsynthesized melamine and obtain carbon nitride blocks; (2) The carbon nitride block was repeatedly calcined at high temperature twice to disperse it into sheets. After cooling, it was dispersed in water or ethanol and then ultrasonically peeled again to obtain a single layer of g-C3N4. (3) HF and tetrabutyl titanate were added to g-C3N4 and ultrasonically mixed. g-C3N4@TiO2 was synthesized by solvothermal method. (4) g-C3N4@TiO2 was calcined at high temperature under a nitrogen atmosphere to obtain oxygen vacancy g-C3N4@TiO2 heterojunction; (5) Preparation of g-C3N4@TiO2 film: g-C3N4@TiO2 is dispersed in water, and the dispersion is dropped onto conductive glass. After heating to evaporate the solvent, a g-C3N4@TiO2 conductive film is formed for imaging analysis of small molecule compounds. (6) Preparation of small molecule antibiotic compound samples: antibiotics were added to blank groundwater as spiked samples, and LDI / MS analysis was performed using oxygen vacancy g-C3N4@TiO2 heterostructure as nanomatrix. (7) Preparation of small molecule compound analysis samples of traditional Chinese medicine: methanol was added to the powder of traditional Chinese medicine, weighed and then extracted by ultrasonication. After the extraction, methanol was used to make up the missing amount. After mixing, it was used as the analysis sample of traditional Chinese medicine. The oxygen vacancy g-C3N4@TiO2 heterostructure was used as the nano matrix for LDI / MS analysis. (8) Preparation of Chinese medicine imaging samples: Fresh Chinese medicines were soaked in antibiotic solutions for 3 days as samples after antibiotic contamination. Untreated Chinese medicines were used as blank samples. The roots of Chinese medicines were cut off, wrapped with OTC glue, and frozen sections were prepared. The sections were attached to g-C3N4@TiO2 conductive film and LDI / MSI were used for distribution imaging analysis.

[0010] Furthermore, in step (1), the carbon nitride precursor is one or more of melamine, urea, and melamine-cyanuric acid in any proportion, and the calcination temperature is 500-650℃ and the calcination time is 2-5 h.

[0011] Furthermore, in step (2), the temperature for repeated calcination is 500-650℃, the calcination time is 1-4 h, the number of calcinations is 1-3, the power of ultrasonic stripping is 100-1000W, and the ultrasonic time is 1-24 h.

[0012] Furthermore, in step (3), the volume ratio of HF to tetrabutyl titanate is 1:7 to 1:5, the amount of g-C3N4 added is 5%-30%, the ultrasonic mixing power is 100-1000W, the ultrasonic time is 0.1-2 h, the temperature used in the solvothermal method is 160-200℃, and the time is 12-36 h.

[0013] Furthermore, in step (4), the calcination temperature of g-C3N4@TiO2 is 500-650℃, and the calcination time is 1-4 h.

[0014] Furthermore, in step (5), the concentration of the g-C3N4@TiO2 dispersion is 3-6 mg / mL, the amount dropped onto the conductive glass is 0.4-1.5 mL, and the heating temperature is 40-80℃.

[0015] Furthermore, the antibiotics added in step (6) are one or more of quinolone antibiotics, macrolide antibiotics, and penicillin antibiotics, wherein the quinolone antibiotics include norfloxacin, gatifloxacin, ciprofloxacin, ofloxacin, and enrofloxacin, the macrolide antibiotics include erythromycin and azithromycin, and the penicillin antibiotics include one or more of penicillin and amoxicillin, and the added concentration is 0.01-1000 μg / mL.

[0016] Furthermore, the antibiotic added in step (8) is one or more of quinolone antibiotics, macrolide antibiotics, and penicillin antibiotics, wherein the quinolone antibiotics include norfloxacin, gatifloxacin, ciprofloxacin, ofloxacin, and enrofloxacin, the macrolide antibiotics include erythromycin and azithromycin, and the penicillin antibiotics include one or more of penicillin and amoxicillin, and the added concentration is 100-1000 μg / mL.

[0017] Compared with the prior art, the advantages of the present invention are as follows: (1) This invention designs a method for preparing heterostructured nanomatrix, prepares a novel oxygen vacancy g-C3N4@TiO2 heterojunction, and uses it for the first time in LDI-MSI.

[0018] (2) Compared with traditional matrices, the LDI-MS method established by the designed oxygen vacancy g-C3N4@TiO2 heterojunction has higher peak intensity and lower background noise. It can be used to detect small molecule compounds such as antibiotics. The detection results have good repeatability and good linearity, and can be used for quantitative analysis.

[0019] (3) This invention breaks through the limitations of traditional organic matrices and single nanomatrices, explores the spatial distribution of antibiotic pollutants and endogenous small molecule compounds in traditional Chinese medicine, and develops a new method for mass spectrometry imaging using novel nanomatrices. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a schematic diagram of the synthesis of oxygen vacancy g-C3N4@TiO2 heterojunction.

[0022] Figure 2Characterization images of the oxygen-vacancy g-C3N4@TiO2 heterojunction synthesized in Example 1 are shown. (A) is the Fourier Transform Infrared (FT-IR) result, (B) is the Ultraviolet-Vis (UV-vis) spectrum, (C) is the X-ray Diffraction (XRD) result, (D) and (E) are the transmission electron microscopy (TEM) results of the uncalcined g-C3N4@TiO2 heterojunction, (F) shows the mechanism of laser desorption / ionization of small molecule compounds assisted by the uncalcined g-C3N4@TiO2 heterojunction, (G) and (H) are the TEM results of the oxygen-vacancy g-C3N4@TiO2 heterojunction, and (I) shows the mechanism of laser desorption / ionization of small molecule compounds assisted by the oxygen-vacancy g-C3N4@TiO2 heterojunction.

[0023] Figure 3 The results of LDI / MS detection of norfloxacin, ciprofloxacin and gatifloxacin in Daming Lake are shown for the oxygen vacancy g-C3N4@TiO2 heterojunction synthesized in Example 1.

[0024] Figure 4 The results of LDI / MS detection of cryptotanshinone in tanshinone were obtained using the oxygen vacancy g-C3N4@TiO2 heterojunction synthesized in Example 2.

[0025] Figure 5 The results of LDI / MSI detection of the oxygen vacancy g-C3N4@TiO2 heterojunction synthesized in Example 2 for imaging analysis of norfloxacin, ciprofloxacin and gatifloxacin residues in reed rhizomes and lotus roots are shown. Detailed Implementation

[0026] The following examples further illustrate the above-mentioned content of the present invention in detail, but it should not be construed as limiting the scope of the present invention to the following examples. All content implemented based on the above-mentioned content of the present invention falls within the scope of the present invention.

[0027] Example 1: ① Synthesis of oxygen vacancy g-C3N4@TiO2 heterojunction: 5g of melamine was placed in a covered alumina crucible and calcined at 500℃ for 5 h. After cooling to room temperature, a yellow solid product was obtained, which was washed several times with deionized water to remove unsynthesized melamine, yielding carbon nitride bulk material. The carbon nitride bulk material was then calcined again at 500℃ for 4 h, followed by ultrasonic exfoliation with water at 100 W for 24 h to obtain g-C3N4 nanosheets. 28 mL of tetrabutyl titanate, 4 mL of HF, and 5% g-C3N4 were mixed and ultrasonically treated at 1000 W for 0.1 h to form a mixture. The mixture was then transferred to a 50 mL polytetrafluoroethylene-lined autoclave and heated at 160℃ for 36 h. After the reaction was completed, the precipitate was collected by centrifugation, soaked in 500 mL of 0.1 M sodium hydroxide for 12 h, washed with water and ethanol, and then dried in an oven at 80 °C for 4 h to obtain white g-C3N4@TiO2 powder. The obtained powder was calcined at 500 °C for 4 h under a nitrogen atmosphere, and the material color changed from white to blackish-green, yielding oxygen vacancy g-C3N4@TiO2 heterojunctions.

[0028] ②Characteristics of oxygen vacancy g-C3N4@TiO2 heterojunction: This invention prepares vacancy g-C3N4@TiO2 heterojunction through a three-step synthesis process. Both the synthesized g-C3N4 and TiO2 are two-dimensional monolayer sheet structures. The synthesis process is as follows: Figure 1 As shown, bulk carbon nitride was first prepared by high-temperature calcination of melamine. Further calcination and ultrasonication yielded two-dimensional sheet-like g-C3N4. Then, TiO2 was prepared via a solvothermal method, followed by high-temperature calcination under nitrogen atmosphere to obtain oxygen-vacancy g-C3N4@TiO2 heterojunctions. The morphology and structure of the synthesized materials were characterized by UV-vis, XRD, FT-IR, and TEM.

[0029] like Figure 2 (A) The FT-IR results show that at 630 cm⁻¹ -1 The broad peak at 800 cm⁻¹ is a peak generated by Ti-O-Ti bonds. -1 The peak at 1230-1630 cm⁻¹ is a characteristic peak of the triazine ring. -1 The multiple peaks appearing at 3000-3300 cm⁻¹ are characteristic peaks formed by C=N and CN heterocycles. -1 The broad peaks appearing at [location] belong to the stretching vibration peaks generated by Ti-OH and NH. Based on the infrared results, the successful synthesis of g-C3N4@TiO2 can be confirmed. The UV-vis results are as follows: Figure 2As shown in (B), g-C3N4 exhibits a strong ultraviolet absorption peak at 300-400 nm, with a maximum absorption wavelength around 320 nm. After g-C3N4 forms a heterojunction with TiO2, the maximum absorption wavelength redshifts to approximately 360 nm, and its maximum absorbance is more than 1.5 times that of g-C3N4 alone. With an LDI / MS laser wavelength of 355 nm, using g-C3N4@TiO2 as the matrix enhances the ultraviolet absorption of the matrix, improves the ionization efficiency of the sample, and thus increases the sensitivity of sample detection. Figure 2 (C) shows the XRD results. GCNs exhibits two characteristic peaks at 13.1° and 27.4°, corresponding to the (001) plane diffraction peak and the interlayer stacking diffraction peak of the conjugated aromatic rings in the (002) plane, respectively. These peaks are consistent with JCPDS: 87-1526, indicating successful synthesis of GCNs. The diffraction peaks of g-C3N4@TiO2 are consistent with the JCPDS: 21-1272 standard card, confirming the presence of TiO2. Almost no diffraction peak is observed at 27.4° for g-C3N4@TiO2, possibly due to the low content of g-C3N4. Furthermore, during the solvothermal synthesis process, g-C3N4 was further exfoliated into monolayers, altering its crystallinity and resulting in indistinct diffraction peaks. Figure 2 As shown in TEM results (D) and (E), the g-C3N4 in g-C3N4@TiO2 exhibits a layered structure, and no bulk structure was observed, proving that the g-C3N4 was completely exfoliated. TiO2 presents as nanosheet structures with a size of approximately 60 nm. After local magnification, a clear lattice fringe boundary can be observed between the GCNs and TNs, proving the formation of a heterostructure in g-C3N4@TiO2. Figure 2 As shown in (G) and (H), the lattice fringes of g-C3N4@TiO2 exhibit partial breakage, indicating the presence of defect states in the material and proving the existence of oxygen vacancy structures. Based on the above characterization results, the synthesis of the oxygen vacancy type g-C3N4@TiO2 heterostructure is confirmed to be successful.

[0030] ③ LDI / MS detection of norfloxacin, ciprofloxacin, and gatifloxacin in Baotu Spring: Norfloxacin, ciprofloxacin, and gatifloxacin were added to blank Baotu Spring water to a concentration of 5-500 μg / L, and mixed with the internal standard dihydrotanshinone (1 μg / mL) at a ratio of 9:1. Using 1 mg / mL g-C3N4@TiO2 aqueous dispersion as the matrix, the samples were analyzed by LDI / MS. The [M+Na] of the analytes was used as the matrix. + Peak areas were calculated, and the samples showed good linearity in the range of 5-500 μg / L, with a linearity coefficient greater than 0.99. The limits of detection (LOD) and quantitation (LOQ) were 1 μg / L and 5 μg / L, respectively. The LOQ detection results are as follows: Figure 3As shown, norfloxacin, ciprofloxacin, and gatifloxacin can still be detected even in the presence of interference, proving that the method has high sensitivity and strong anti-interference ability.

[0031] Example 2: ① Synthesis of oxygen vacancy g-C3N4@TiO2 heterojunction: 5g of melamine-cyanuric acid composite was placed in a covered alumina crucible and calcined at 650℃ for 2 h. After cooling to room temperature, a yellow solid product was obtained, which was washed several times with deionized water to remove unsynthesized melamine, yielding carbon nitride bulk material. The carbon nitride bulk material was then calcined twice more at 650℃ for 2 h, followed by ultrasonic exfoliation with water at 500 W for 1 h to obtain g-C3N4 nanosheets. 25 mL of tetrabutyl titanate, 4 mL of HF, and 15% g-C3N4 were mixed and ultrasonically treated at 500 W for 2 h to form a mixture. The mixture was then transferred to a 50 mL polytetrafluoroethylene-lined autoclave and heated at 180℃ for 18 h. After the reaction was completed, the precipitate was collected by centrifugation, soaked in 500 mL of 0.1 M sodium hydroxide for 12 h, washed with water and ethanol, and then dried in an oven at 80 °C for 4 h to obtain white g-C3N4@TiO2 powder. The obtained powder was calcined at 650 °C for 2 h under a nitrogen atmosphere, and the material color changed from white to blackish-green, obtaining oxygen vacancy g-C3N4@TiO2 heterojunctions.

[0032] ② Quantitative analysis of cryptotanshinone in Salvia miltiorrhiza extract: 0.3 g of Salvia miltiorrhiza powder was added to 50 mL of methanol, weighed, and then subjected to ultrasonic extraction for 30 min. After extraction, the missing amount was replenished with methanol. The extract was mixed with the internal standard erythromycin solution at a 1:1 ratio and used as the sample for analysis. A solution of 10-150 μg / mL cryptotanshinone was prepared and mixed with the internal standard erythromycin solution at a 1:1 ratio and used as the sample for cryptotanshinone quantification. LDI / MS analysis was performed using oxygen vacancy g-C3N4@TiO2 heterostructures as the nanomatrix. The [M+Na] of the analyte was used as the nanomatrix. + Peak areas were calculated, and cryptotanshinone showed good linearity in the range of 10-150 μg / mL, with a linearity coefficient greater than 0.99. The LOD and LOQ were 1.5 μg / mL and 2.5 μg / mL, respectively. The analytical results of the tanshinone extract are as follows: Figure 4 As shown, cryptotanshinone in the tanshinone extract was quantified using the standard curve, and the result was 10.86 μg / mL. This demonstrates that the obtained oxygen vacancy g-C3N4@TiO2 heterojunction can be used for the qualitative and quantitative analysis of endogenous small molecule compounds in traditional Chinese medicine.

[0033] Example 3: ① Synthesis of oxygen vacancy g-C3N4@TiO2 heterojunction: 5g of urea was placed in a covered alumina crucible and calcined at 650℃ for 3 h. After cooling to room temperature, a yellow solid product was obtained, which was washed several times with deionized water to remove unsynthesized melamine, yielding carbon nitride bulk material. The carbon nitride bulk material was then calcined twice more at 650℃ for 1 h, followed by ultrasonic exfoliation with water at 100 W for 1 h to obtain g-C3N4 nanosheets. 20 mL of tetrabutyl titanate, 4 mL of HF, and 20% g-C3N4 were mixed and ultrasonically treated at 100 W for 24 h to form a mixture. The mixture was then transferred to a 50 mL polytetrafluoroethylene-lined autoclave and heated at 200℃ for 12 h. After the reaction was completed, the precipitate was collected by centrifugation, soaked in 500 mL of 0.1 M sodium hydroxide for 12 h, washed with water and ethanol, and then dried in an oven at 80 °C for 4 h to obtain white g-C3N4@TiO2 powder. The obtained powder was calcined at 650 °C for 1 h under a nitrogen atmosphere, and the material color changed from white to blackish-green, obtaining oxygen vacancy g-C3N4@TiO2 heterojunctions.

[0034] ② LDI / MSI detection of norfloxacin, ciprofloxacin, and gatifloxacin distribution in reed rhizomes and lotus roots: Fresh blank reeds and lotus roots were soaked in antibiotic solutions for 3 days as samples after antibiotic contamination. Reed rhizome and lotus root segments were cut, coated with OTC gel, and cryosectioned. The sections were then attached to a g-C3N4@TiO2 conductive film, and LDI / MSI distribution imaging analysis was performed. The results are as follows: Figure 5 As shown, the soaked reed roots and lotus root nodes all exhibited hydrogenation, sodium addition, and potassium addition peaks for three quinolone drugs. This demonstrates that fresh plants can adsorb antibiotics from the aquatic environment and generate detection signals. Simultaneously, the imaging results of the lotus root nodes and reed roots also indicate that the synthesized GCNs@TNs nanomatrix has good film-forming properties, can be uniformly dispersed on ITO conductive glass, and assists in the laser desorption / ionization of sliced ​​samples to generate effective mass spectrometry detection signals.

[0035] This invention discloses a laser desorption / ionization mass spectrometry (LDI / MS) and imaging (LDI / MSI) method for small molecule drugs such as antibiotics, based on a g-C3N4@TiO2 oxygen-vacancy heterojunction matrix. Compared with traditional organic matrices, the g-C3N4@TiO2 heterojunction used in this method has advantages such as low background interference, high robustness, high stability, high sensitivity, and high dispersion uniformity. Simultaneously, the presence of the heterostructure avoids the problems of absorbance difference and rapid carrier recombination caused by a single nanomatrix. The obtained g-C3N4@TiO2 heterojunction can not only be used for LDI / MS detection of quinolone antibiotics in environmental water samples and LDI / MS detection of endogenous small molecules in Danshen (Salvia miltiorrhiza), but can also be uniformly dispersed on ITO conductive glass slides for imaging analysis of antibiotic contamination in traditional Chinese medicine. This invention provides a new method for the detection of small molecule compounds in complex samples and the distribution detection of pollutants and endogenous small molecule compounds in traditional Chinese medicine, and also provides new ideas for the development of novel nanomatrices. The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. An application of an oxygen vacancy-type g-C3N4@TiO2 heterojunction, characterized in that, The heterostructures of g-C3N4 and TiO2 were synthesized for mass spectrometry detection and analysis of small molecule antibiotic compounds, and for imaging analysis of the distribution of pollutants and endogenous substances in traditional Chinese medicine. The application method of oxygen vacancy type g-C3N4@TiO2 heterojunction includes the following steps: (1) The carbon nitride precursor powder was directly calcined at high temperature to obtain a yellow solid product, and washed several times with deionized water to remove the unsynthesized melamine and obtain carbon nitride blocks; (2) The carbon nitride block was repeatedly calcined at high temperature twice to disperse it into sheets. After cooling, it was dispersed in water or ethanol and then ultrasonically peeled again to obtain a single layer of g-C3N4. (3) HF and tetrabutyl titanate were added to g-C3N4 and ultrasonically mixed. g-C3N4@TiO2 was synthesized by solvothermal method. (4) g-C3N4@TiO2 was calcined at high temperature under a nitrogen atmosphere to obtain oxygen vacancy g-C3N4@TiO2 heterojunction; (5) Preparation of g-C3N4@TiO2 film: g-C3N4@TiO2 is dispersed in water, and the dispersion is dropped onto conductive glass. After heating to evaporate the solvent, a g-C3N4@TiO2 conductive film is formed for imaging analysis of small molecule compounds. (6) Preparation of small molecule antibiotic compound samples: antibiotics were added to blank groundwater as spiked samples, and LDI / MS analysis was performed using oxygen vacancy g-C3N4@TiO2 heterostructure as nanomatrix. (7) Preparation of small molecule compound analysis samples of traditional Chinese medicine: methanol was added to the powder of traditional Chinese medicine, weighed and then extracted by ultrasonication. After the extraction, methanol was used to make up the missing amount. After mixing, it was used as the analysis sample of traditional Chinese medicine. The oxygen vacancy g-C3N4@TiO2 heterostructure was used as the nano matrix for LDI / MS analysis. (8) Preparation of Chinese medicine imaging samples: Fresh Chinese medicines were soaked in antibiotic solutions for 3 days as samples after antibiotic contamination. Untreated Chinese medicines were used as blank samples. The roots of Chinese medicines were cut off, wrapped with OTC glue, and frozen sections were prepared. The sections were attached to g-C3N4@TiO2 conductive film and LDI / MSI were used for distribution imaging analysis.

2. The application of the oxygen vacancy type g-C3N4@TiO2 heterojunction according to claim 1, characterized in that: In step (1), the carbon nitride precursor is one or more of melamine, urea, and melamine-cyanuric acid in any proportion, and the calcination temperature is 500-650℃ and the calcination time is 2-5 h.

3. The application of the oxygen vacancy type g-C3N4@TiO2 heterojunction according to claim 1, characterized in that: Step (2) involves repeated calcination at a temperature of 500-650℃, a calcination time of 1-4 h, and 1-3 calcinations. The ultrasonic stripping power is 100-1000W, and the ultrasonic time is 1-24 h.

4. The application of the oxygen vacancy type g-C3N4@TiO2 heterojunction according to claim 1, characterized in that: In step (3), the volume ratio of HF to tetrabutyl titanate is 1:7 to 1:5, the amount of g-C3N4 added is 5%-30%, the ultrasonic mixing power is 100-1000W, the ultrasonic time is 0.1-2 h, the temperature used in the solvothermal method is 160-200℃, and the time is 12-36 h.

5. The application of the oxygen vacancy type g-C3N4@TiO2 heterojunction according to claim 1, characterized in that, In step (4), the calcination temperature of g-C3N4@TiO2 is 500-650℃, and the calcination time is 1-4 h.

6. The application of the oxygen vacancy type g-C3N4@TiO2 heterojunction according to claim 1, characterized in that, In step (5), the concentration of the g-C3N4@TiO2 dispersion is 3-6 mg / mL, the amount dropped onto the conductive glass is 0.4-1.5 mL, and the heating temperature is 40-80℃.

7. The application of the oxygen vacancy type g-C3N4@TiO2 heterojunction according to claim 1, characterized in that, The antibiotics added in step (6) are one or more of quinolone antibiotics, macrolide antibiotics, and penicillin antibiotics. Among them, quinolone antibiotics include norfloxacin, gatifloxacin, ciprofloxacin, ofloxacin, and enrofloxacin; macrolide antibiotics include erythromycin and azithromycin; and penicillin antibiotics include one or more of penicillin and amoxicillin. The added concentration is 0.01-1000 μg / mL.

8. The application of the oxygen vacancy type g-C3N4@TiO2 heterojunction according to claim 1, characterized in that, The antibiotics added in step (8) are one or more of quinolone antibiotics, macrolide antibiotics, and penicillin antibiotics. Among them, quinolone antibiotics include norfloxacin, gatifloxacin, ciprofloxacin, ofloxacin, and enrofloxacin; macrolide antibiotics include erythromycin and azithromycin; and penicillin antibiotics include one or more of penicillin and amoxicillin. The added concentration is 100-1000 μg / mL.

Citation Information

Patent Citations

  • Photoelectrochemical adaptor sensor as well as preparation method and application thereof

    CN108845009A

  • Application of molybdenum disulfide / graphite-phase nitrogen carbide composite material in matrix-assisted laser desorption ionization time-of-flight mass spectrometry detection

    CN110940724A

  • Preparation method of defective titanium dioxide / ultrathin carbon nitride / defective titanium dioxide Z-type heterojunction photocatalyst

    CN114345393A